Preparation and Characterization of Nanofibrillated Cellulose from Bamboo Fiber via Ultrasonication Assisted by Repulsive Effect - Zhijun Hu; Rui Zhai; Jing Li; Yan Zhang; Jiang Lin (International Journal of Polymer Science)
Nanofibrillated celluloses (NFCs) have recently drawn much attention because of their exceptional physicochemical properties. However, the existing preparation procedures either produce low yields or severely degrade the cellulose and, moreover, are not energy efficient. The purpose of this study was to develop a novel process using ultrasonic homogenization to isolate fibrils from bamboo fiber (BF) with the assistance of negatively charged entities. The obtained samples were characterized by the degree of substitution (DS) of carboxymethyl, Fourier-transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), thermogravimetric analysis, and transmission electron microscopy (TEM). The results showed that an NFC yield could be obtained above 70% through this route. The enzyme hydrolysis could enhance the surface charge of the fiber, and mechanical activation facilitates an increase in the DS. The disintegrating efficiency of the cellulose fibrils significantly depended on the input power of ultrasonication and the DS. FT-IR spectra confirmed the occurrence of the carboxymethylation reaction based on the appearance of the characteristic signal for the carboxyl group. From XRD analysis, it was observed that the presence of the carboxyl groups makes the isolation more efficient attributed to the ionic repulsion between the carboxylate groups of the cellulose chains.